Immunosuppressive therapies in scorpion envenomation: new perspectives for treatment - Reis, Mouzarllem Barros; Arantes, Eliane Candiani (Frontiers in Toxicology, 2024)
Scorpion envenoming is a relevant and neglected public health problem in some countries. The use of antivenom is widespread in many regions, targeting specific species of scorpions. However, the uncontrolled proliferation and adaptation of these animals to urban environments, combined with limited access to treatments in remote areas and delays in antivenom administration contribute to a significant number of fatalities from scorpion-related incidents. In recent decades, new research has revealed that the immune system plays an important role in triggering immunopathological reactions during scorpion envenoming, which places it as a therapeutic target; however, few clinical studies have been conducted. This work provides a review of the main immunopathological aspects of scorpion envenoming, as well as the clinical trials conducted to date on the use of corticosteroids for the treatment of scorpionism. We highlight emerging treatment perspectives as well as the need for further clinical trials. The use of corticosteroids in scorpionism, when appropriate, could significantly enhance access to treatment and help reduce fatalities associated with scorpion stings.